The Political Management of HIV and AIDS in South Africa - Fourie, P. author. aut Link
XIX, 240 p.
Keywords: This book analyzes successive governments' management of the AIDS epidemic in South Africa. The book covers the years 1982-2005, using expert thinking regarding public policy making to identify gaps in the public sector's handling of the epidemic. It highlights critical lessons for policy makers and other public health managers.